2008
DOI: 10.1103/physrevlett.100.226602
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Transfer Torques in Antiferromagnetic Metals from First Principles

Abstract: In spite of the absence of a macroscopic magnetic moment, an antiferromagnet is spin-polarized on an atomic scale. The electric current passing through a conducting antiferromagnet is polarized as well, leading to spin-transfer torques when the order parameter is textured, such as in antiferromagnetic noncollinear spin valves and domain walls. We report a first principles study on the electronic transport properties of antiferromagnetic systems. The current-induced spin torques acting on the magnetic moments a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 34 publications
4
96
0
Order By: Relevance
“…(17) which leads to an extremely fast integration time ∝ log L (In practice, one starts with an extremely small piece of material described by Eq. (33) and recursively doubles it size using Eqs. (16,17) until obtaining the full width L of the layer).…”
Section: Continuous Random Matrix Theory (Crmt)mentioning
confidence: 99%
See 1 more Smart Citation
“…(17) which leads to an extremely fast integration time ∝ log L (In practice, one starts with an extremely small piece of material described by Eq. (33) and recursively doubles it size using Eqs. (16,17) until obtaining the full width L of the layer).…”
Section: Continuous Random Matrix Theory (Crmt)mentioning
confidence: 99%
“…Many different approaches have been developed, ranging from purely quantum 16,17 to semi-classical Boltzmann equation [18][19][20] , (generalized) circuit theory [21][22][23][24][25][26][27] or Random Matrix Theory (RMT) 28,29 or full ab-initio (density functional theory) calculations [30][31][32][33] . A good understanding has now been reached of the respective domains of applicability and links between the various approaches 26,29 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been predicted theoretically that spin-transfer torque (STT) can act on AFM, causing reorientation of its spin configuration, domain wall motion and stable oscillation or precession of the Neel vector [18][19][20][21] . Several follow-up experiments on exchange-biased spin-valves [22][23][24][25] have shown that current induced STT is able to affect the exchange bias at the FM/AFM interface, indirectly suggesting the presence of STT effect in AFM.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new direction in spintronics has been proposed based on nonrelativistic [1][2][3][4][5] and relativistic [6,7] spin-transport phenomena in which antiferromagnets (AFMs) complement or replace ferromagnets (FMs) in active parts of the device. AFMs have for decades played a passive role in conventional spin-valve structures where they provide pinning of the reference FM layer [8].…”
Section: Introductionmentioning
confidence: 99%